Sulfide and methane production in sewer sediments. (1st March 2015) - Liu, Yiwen; Ni, Bing-Jie; Ganigué, Ramon; Werner, Ursula; Sharma, Keshab R.; Yuan, Zhiguo
Abstract: Recent studies have demonstrated significant sulfide and methane production by sewer biofilms, particularly in rising mains. Sewer sediments in gravity sewers are also biologically active; however, their contribution to biological transformations in sewers is poorly understood at present. In this study, sediments collected from a gravity sewer were cultivated in a laboratory reactor fed with real wastewater for more than one year to obtain intact sediments. Batch test results show significant sulfide production with an average rate of 9.20 ± 0.39 g S/m 2 ·d from the sediments, which is significantly higher than the areal rate of sewer biofilms. In contrast, the average methane production rate is 1.56 ± 0.14 g CH4 /m 2 ·d at 20 °C, which is comparable to the areal rate of sewer biofilms. These results clearly show that the contributions of sewer sediments to sulfide and methane production cannot be ignored when evaluating sewer emissions. Microsensor and pore water measurements of sulfide, sulfate and methane in the sediments, microbial profiling along the depth of the sediments and mathematical modelling reveal that sulfide production takes place near the sediment surface due to the limited penetration of sulfate. In comparison, methane production occurs in a much deeper zone below the surface likely due to the better penetration of soluble organic carbon. Modelling results illustrate the dependency of sulfide and methane productions on the bulk sulfate and soluble organic carbon concentrations can be well described with half-order kinetics. Graphical abstract: Highlights: Sewer sediments are a significant source of sulfide and methane. Sulfide production occurs near sediment surface due to limited sulfate penetration. CH4 production also occurs closer to sediment surface but in a much thicker zone. In-sediment sulfide/CH4 production rates can be described by half-order kinetics.